The impact of the solar energy on the load profile of the building - Zhang, Jun (2013)
With the rapid depletion of fossil fuel reserves, it is feared that the world will soon run out of its energy resources. This is a matter of concern for developing countries whose economy heavily leans on its use of energy. Under the circumstances it is highly desirable that renewable energy resources should be utilized with maximum conversion efficiency to cope with the ever increasing energy demand. The global economic and political conditions that tend to make countries more dependent on their own energy resources have caused growing interest in the development and use of renewable energy based technologies. In terms of its environmental advantages, renewable energy sources generate electricity with insignificant contribution of carbon dioxide or other greenhouse gases to the atmosphere and they produce no pollutant discharge on water or soil and hence power generation from renewable becomes very important.